Enhancement of extracellular pullulanase production by Raoultella planticola DSMZ 4617 using optimized medium based on sago starch - Siew, Ling Hii; Tau, Chuan Ling; Mohamad, Rosfarizan; Ariff, Arbakariya (Bentham Science Publishers, 2008)
Enhancement of pullulanase production by Raoultella planticola DSMZ 4617 using optimized medium formulation was investigated in batch fermentation using 500-mL shake flask. The fermentations were carried out, firstly, to search for a suitable cultivation medium for enzyme production and followed by the evaluations on the influence of carbon and nitrogen sources and also initial culture pHs on the secretion of pullulanase by this bacterium. The modified mineral Czapek medium was found suitable to produce substantially high activity of pullulanase (320 times higher) as compared to ‘Ohba-Ueda’ medium. This bacterium was found superior in pullulanase production using sago starch and peptone as carbon and nitrogen sources, respectively. Using the optimized medium, the bacterium produced 0.95 U/mL of pullulanase at initial culture pH of 7 and incubation temperature of 30oC.